Effect of Conventional Lifestyle Interventions on Type 2 Diabetes Incidence by Glucose-Defined Prediabetes Phenotype: An Individual-Participant Data Meta-analysis of Randomized Controlled Trials. - Sathish, Thirunavukkarasu; Khunti, Kamlesh; Narayan, K M Venkat; Mohan, Viswanathan; Davies, Melanie J; Yates, Thomas; Oldenburg, Brian; Thankappan, Kavumpurathu R; Tapp, Robyn J; Bajpai, Ram; Anjana, Ranjit Mohan; Weber, Mary B; et al. (Diabetes Care)
To examine whether the effect of conventional lifestyle interventions on type 2 diabetes incidence differs by glucose-defined prediabetes phenotype. We searched multiple databases until 1 April 2023 for randomized controlled trials that recruited people with isolated impaired fasting glucose (i-IFG), isolated impaired glucose tolerance (i-IGT), and impaired fasting glucose plus impaired glucose tolerance (IFG+IGT). Individual-participant data were pooled from relevant trials and analyzed through random-effects models with use of the within-trial interactions approach. Four trials with 2,794 participants (mean age 53.0 years, 60.7% men) were included: 1,240 (44.4%), 796 (28.5%), and 758 (27.1%) had i-IFG, i-IGT, and IFG+IGT, respectively. After a median of 2.5 years, the pooled hazard ratio for diabetes incidence in i-IFG was 0.97 (95% CI 0.66, 1.44), i-IGT 0.65 (0.44, 0.96), and IFG+IGT 0.51 (0.38, 0.68; Pinteraction = 0.01). Conventional lifestyle interventions reduced diabetes incidence in people with IGT (with or without IFG) but not in those with i-IFG. [Abstract copyright: © 2023 by the American Diabetes Association.]
ORCID Source: Crossref Path: /0000-0002-1227-2703/work/141522153
Keywords: International Collaborator(s)